Platform-Independent Optimization of Pump Power Threshold for Microcomb Generation - Souleymane Diallo; Curtis R. Menyuk; Yanne K. Chembo (IEEE Photonics Journal, 2022)
Kerr optical frequency combs have found various applications in science and technology, and minimizing their pump power has become an important area of research. These combs are generated using a wide variety of platforms, with a size ranging from micrometers to millimeters, and quality factors ranging from millions to billions. It is therefore not trivial to assess the pump power requirements for comb generation when they have such a large diversity in terms of resonator properties and pump configurations. We propose a suitably normalized threshold pump power as a metric to optimize Kerr comb generation independently of the platform. This method allows one to evaluate the minimum threshold power solely based on the properties of the bare resonator, and independently of dispersion, detuning or coupling considerations. In order to confirm the validity of this approach, we experimentally demonstrate Kerr comb generation in a millimeter-size magnesium fluoride whispering-gallery mode resonator with a threshold pump power of only 1.2 mW, which is one of the lowest pump powers reported to date for a mm-size resonator.